Use of acetate crowns for the fabrication of resin crowns on primary teeth: Case report - Palomino Rios, Ethel Violeta (2021)
Being one of the restoration options the use of the acetate crown technique, this was chosen due to the aesthetic results it offers and its few clinical steps. Thus fulfilling our objective of maintaining the integrity of the pieces and keeping them in their space, through the use of resin crowns made under this technique. The methodology used was the clinical case report in a male patient aged 2 years 09 months with a diagnosis of dental caries, where resin crowns were performed using the acetate crown technique. For the clinical evaluation at 12 months, the evaluation criteria for direct and indirect restorations according to the World Dental Federation were used. They did not present fracture and caries recurrence. Crowns made with this technique were well accepted due to their imperceptible results, low cost and shorter clinical time. Therefore, the use of this technique would be a treatment option, but more studies are required to determine its long-term benefits